Morphometric Characters and Sex Ratio of the Freshwater Garfish, Xenentodon Cancila Collected From Different Waters of Jashore, South-Western Bangladesh (Journal of Bio-Science, 2021)
The freshwater garfish, Xenentodon cancila is one of the important food fish in Bangladesh. The size class distribution, length-weight relationships, and sex ratio of X. cancila are described in the present study. A total of 138 specimens were collected randomly for a year from the local fish markets and/or direct from fishermen who fish primarily in nearby waters (Beel, Canal and Baor) of Jashore, southwestern Bangladesh. Most individuals were collected in the rainy season and their mean size was larger compare to the other two seasons (summer and winter). The maximum size recorded 254.1 mm total length (TL) and 38.05 g body weight (BW). The mean TL and BW were 166.35±38.17 mm and 11.16±7.47g, respectively. Most of the individuals belonged to the size class of 141-180 mm. The length-weight relationship (LWR) was strongly correlated as the regression value was 0.876 and the relationships were linear in both sexes. The allometric coefficient ‘b’ of the LWR indicated nearly positive allometric growth and the value was 2.98. The male fishes were dominant over females and the ratio was 1: 0.77. These research outcomes would be useful for the researcher to better understand the biological aspects of freshwater garfish in the nearby waters of Jashore area in south-western Bangladesh.J. Bio-Sci. 29(1): 23-31, 2021 (June)